A Novel Strategy for Detecting Recent Horizontal Gene Transfer and Its Application to Rhizobium Strains - Li, Xiangchen; Tong, Wenjun; Wang, Lina; Rahman, Siddiq Ur.; Wei, Gehong; Tao, Shiheng (Frontiers in Microbiology, 2018)
Recent horizontal gene transfer (HGT) is crucial for enabling microbes to rapidly adapt to their novel environments without relying upon rare beneficial mutations that arise spontaneously. For several years now, computational approaches have been developed to detect HGT, but they typically lack the sensitivity and ability to detect recent HGT events. Here we introduce a novel strategy, named RecentHGT. The number of genes undergoing recent HGT between two bacterial genomes was estimated by a new algorithm derived from the expectation-maximization algorithm and is based on the theoretical sequence-similarity distribution of orthologous genes. We tested the proposed strategy by applying it to a set of 10 Rhizobium genomes, and detected several large-scale recent HGT events. We also found that our strategy was more sensitive than other available HGT detection methods. These HGT events were mainly mediated by symbiotic plasmids. Our new strategy can provide clear evidence of recent HGT events and thus it brings us closer to the goal of detecting these potentially adaptive evolution processes in rhizobia as well as pathogens.